2021
DOI: 10.1108/ec-11-2020-0637
|View full text |Cite
|
Sign up to set email alerts
|

Study of isolation effectiveness of nuclear reactor building with three-dimensional seismic base isolation

Abstract: PurposeIn recent years, three-dimensional (3D) seismic base isolation system has been studied extensively. This paper aims to propose a new 3D combined isolation bearing (3D-CIB) to mitigate the seismic response in both the horizontal and vertical directions.Design/methodology/approachThe new 3D-CIB composed of laminated rubber bearing coupled with combined disk spring bearing (CDSB) was proposed. Comprehensive analysis of constitution and theoretical derivation for 3D-CIB were presented. The advantage of CDSB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nie et al (2022) developed a novel 3D isolated bearing that can reduce horizontal and vertical seismic responses of space double-layer cylindrical reticulated shells (SDLCRS). Zhu et al (2021) proposed a new 3D composite isolated bearing (3D-CIB), which consists of a laminated rubber bearing and composite coil spring bearing. The results show that 3D-CIB can effectively reduce the seismic response of the superstructure in horizontal and vertical directions.…”
Section: Introductionmentioning
confidence: 99%
“…Nie et al (2022) developed a novel 3D isolated bearing that can reduce horizontal and vertical seismic responses of space double-layer cylindrical reticulated shells (SDLCRS). Zhu et al (2021) proposed a new 3D composite isolated bearing (3D-CIB), which consists of a laminated rubber bearing and composite coil spring bearing. The results show that 3D-CIB can effectively reduce the seismic response of the superstructure in horizontal and vertical directions.…”
Section: Introductionmentioning
confidence: 99%
“…However, earlier studies focused on horizontal isolation systems and ignored the influence of seismic motion in the vertical direction. With the improvement of isolation systems, many experts and scholars began to focus on three-dimensional isolation systems [18][19][20]. Liang et al proposed and tested three-dimensional isolation bearings and found that they can effectively isolate horizontal and vertical ground motions [21].…”
Section: Introductionmentioning
confidence: 99%